Peran Skrining Awal Kadar Trigliserida pada Kelompok Usia Dewasa di Kelurahan Krendang, Jakarta Barat - Siufui Hendrawan; Alexander Halim Santoso; Jeffry Luwito; Edwin Destra; Agustina Agustina (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Triglycerides are a type of fat found in the blood and serve as a source of energy. When levels rise beyond normal limits, triglycerides can become a risk factor for various health disorders. Hypertriglyceridemia requires prevention and early detection as essential steps in reducing the risk of metabolic disorders. This community service program utilized the Plan-Do-Check-Act (PDCA) approach to educate adults in the Krendang area on the importance of triglyceride screening and adopting a healthy lifestyle. The health education and routine screenings provided successfully increased public awareness of the risks associated with high triglyceride levels and encouraged healthier lifestyle changes. Program results showed that the community became more proactive in monitoring triglyceride levels and adopting healthy behaviors such as balanced diets and regular physical activity. Triglyceride screening and health education play a vital role in preventing metabolic disorders caused by hypertriglyceridemia, supporting preventive efforts to improve public health